On the Value of the Chinese Pre-Qin Confucian Thought of “Harmony” for Modern Public Mental Health - Li, Yingying; Cui, Huaqian (Frontiers in Psychology, 2022)
The Chinese pre-Qin Confucianism puts forward the concept of "Harmony", covering "Balanced Harmony", "External harmony" and "Internal Harmony", etc. "Balanced Harmony" means achieving balance by pursuing the golden mean; "External Harmony" refers to forming a harmonious external relationship with others, with society and with nature through "benevolent love"; "Internal Harmony" is to maintain individual physical and mental harmony within oneself by way of "seeking from the heart". Among them, "Balanced Harmony" is the fundamental path to maintain harmony, while "External Harmony" and "Internal Harmony" are the two basic approaches to maintain harmony, the trinity of which constitutes the methodology of valuing "Harmony". As one of the backbones of traditional Chinese culture, the concept of "Harmony" of pre-Qin Confucianism not only has had a far-reaching impact on the spiritual temperament, psychological status, mode of thinking and moral personality of the Chinese nation in history, but also provides insights for public mental health in modern times worldwide, containing many ideas from which Western public mental health can profit.